2004
DOI: 10.1086/379872
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Effects in Reflecting Coronagraphs for White‐Light Applications in Astronomy

Abstract: The properties of metal thin films have been largely overlooked in discussions of the technical limitations and problems that arise in the field of direct detection of exoplanets. Here, polarization properties and anisotropy properties of highly reflecting thin metal films are examined within the context of the requirements for the ultralow-scattered-light system performance of coronagraphs applied to space and ground-based high-contrast, whitelight astronomy. Wavelength-dependent optical constants for highly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 21 publications
2
45
0
Order By: Relevance
“…Sources of polarization-induced anisoplanatism are identified, examples derived and the role of the complex (real and imaginary) vector waves is presented. This paper is a continuation of our previous work 1,2,3,4,5,6 on the subject of physical optics vector wave propagation through a typical astronomical telescope optical system and the affects of this propagation on scientific astronomical data quality. In 2004, Breckinridge and Oppenheimer 3 showed that polarization introduced by image forming optics internal to a telescope & coronagraph optical system adds noise to the system and masks signatures important for the characterization of exoplanets.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Sources of polarization-induced anisoplanatism are identified, examples derived and the role of the complex (real and imaginary) vector waves is presented. This paper is a continuation of our previous work 1,2,3,4,5,6 on the subject of physical optics vector wave propagation through a typical astronomical telescope optical system and the affects of this propagation on scientific astronomical data quality. In 2004, Breckinridge and Oppenheimer 3 showed that polarization introduced by image forming optics internal to a telescope & coronagraph optical system adds noise to the system and masks signatures important for the characterization of exoplanets.…”
Section: Introductionmentioning
confidence: 76%
“…However, any surface in the entire optical path that introduces partial polarization, either circular or linear will distort the PSF and will increase scattered light. Optical filters, diffraction gratings 18 , fold mirrors 19,20 needed for packaging, and the necessary powered optical elements 21 to control geometric aberrations introduce internal polarization to modify the PSF. Such polarization induced aberration needs to be understood in detail to optimize the detection and characterization of exoplanets using coronagraphy and astrometry.…”
Section: Image Formation Is An Interference Phenomenonmentioning
confidence: 99%
“…Several coronagraph architectures have been proposed [7][8][9][10][11][12][13] . Each one of these will have degraded performance because of Fresnel polarization apodization.…”
Section: Polarization Compensationmentioning
confidence: 99%
“…The ring mask, shown at plane 4 is not a powered element. Although the telescope primary may be quite large, 8 meters as planned in NASA exoplanet missions [7][8][9][10][11][12] , the mitigation of Fresnel Polarization can be done at a much smaller and convenient pupil plane such as at plane 4 where the ring mask is located. The functions of the polarization compensator and ring mask can be combined, as we are describing under this effort.…”
Section: Polarization Compensation In Coronagraph System Design Consimentioning
confidence: 99%
“…13 The dependence of IP on the incident angles of the mirror has already been estimated and presented for silver, gold, and aluminum coating. 14 A model has been developed to estimate the IP at the focus of a very large telescope (VLT). 15 They use Stokes/Mueller formalism to estimate the IP for the telescope and the Nasmyth adaptive optics system (NACO) for the K s band.…”
Section: Introductionmentioning
confidence: 99%